Continual exposure to limited input: DOM in Heritage Romanian (Romanian Studies Today, 2024)
This paper explores whether there is evidence for reduced input effects on differential object marking in heritage Romanian. The 50 participants (age range 5;07 – 25;07) are all Romanian-French bilinguals born to Romanian families living in France. The analysis of DOM use in their narratives identified three developmental stages. Until age 7, DOM use is monolingual-like, but during the first school years, there is a significant decrease in DOM use followed, in adulthood, by a reversion to monolingual-like use. The adult heritage speakers use DOM similarly to Romanianspeaking adults living in the homeland. The paper discusses these findings in relation to reduced input effects in heritage languages. The claim is that these effects reach their peak after onset of schooling which coincides with a decrease in input amount in the heritage language and a shift in language dominance. The effects of reduced input can, however, be overcome in adulthood, as long as there is continual exposure to the heritage language over time.
Keywords: differential object marking; heritage Romanian; reduced input; incomplete acquisition; continual exposure